Provision and access to health services in Mozambique: An exploratory study on accountability and relations between health providers and users in Monapo district - Gonçalves, Euclides (POTENCIAR Programme, 2021)
This exploratory research set out to survey possible points of entry for POTENCIAR programme interventions and gather methodological insights for the ethnographic research component of the programme’s analytical strategy. It wil be used alongside other analytical studies undertaken by POTENCIAR (including the health sector analysis and the political economy analyses) to identify and design programme interventions. Following an inductive method, the team sought to assess the conditions and processes of health care provision and access from the perspective of health providers and residents in Monapo district in Nampula Province, northern Mozambique (POTENCIAR will implement its first PAI in Nampula province). To gain insights into accountability relations in the health sector, the team focused on the administrative and social institutions where health providers and users interact. The study asks the following question: From grounded perspectives of health providers and residents in Monapo district, what are the accountability issues in the provision and access to health services?
Keywords: *non-public; Ethnographic Studies; G - Mozambique / Moçambique; GD - Monapo; L - english / inglês; M - ethnography / etnografia; accountability / responsabilização; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health / saúde

Com quem podemos contar? Autoridade, Empoderamento e Responsabilização em Moçambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (Portuguese Translation of IDS Working Paper 546, Maputo: Instituto de Estudos Sociais e Económicos, 2021)
Neste artigo, usamos 'diários de governação' para analisar as interações entre pessoas pobres e autoridades em contextos de Fragilidade, Conflitos e Violência (FCVAS) em Moçambique. Questionamos os significados de empoderamento e responsabilização, sob ponto de vista de pessoas pobres e marginalizadas, e procuramos perceber como essas pessoas vêem as instituições que as governam, incluindo as que as providenciam bens e serviços básicos, entre os quais os de saúde e segurança. As conclusões mostram que, mesmo que as percepções e, com elas, os conceitos de empoderamento e responsabilização que emergiram, não difiram significativamente dos identificados na literatura, em termos de ação e mobilização há diferenças. Constatamos que, nos nossos locais de pesquisa, as pessoas raramente se mobilizam, mesmo com a má prestação de serviços básicos e a prevalência de injustiças. Muitos consideram-se 'incapazes' de influenciar ou forçar as 'autoridades' a responderem às suas preocupações e demandas. Por 'Autoridade Pública' entendem qualquer entidade ou pessoa capaz de resolver os problemas da comunidade, enquanto Estado, geralmente reconhecido como 'Autoridade', é percebido como indistinto do Partido Frelimo e do Governo, mas também é visto como um pai, embora ausente, e aquele que se esquece e abandona os seus filhos.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Who Can We Count On? Authority, Empowerment and Accountability in Mozambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (IDS Working Paper 546, Brighton: Institute of Development Studies, 2021)
In this paper, we explore the use of a governance diaries methodology to investigate poor households’ interactions with authority in fragile, conflict and violence-affected settings in Mozambique. The research questioned the meanings of empowerment and accountability from the point of view of poor and marginalised people, with the aim of understanding what both mean for them, and how that changes over time, based on their experiences with governance. The study also sought to record how poor and marginalised households view the multiple institutions that govern their lives; providing basic public goods and services, including health and security; and, in return, raise revenues to fund these services. The findings show that, even if the perceptions and, with them, the concepts of empowerment and accountability that emerged do not differ significantly from those identified in the literature, in terms of action and mobilisation there are distinctions. In our research sites we found that people rarely mobilise, even faced with prevalent injustices and poor basic service provision. Many claim to be ‘unable’ to influence or force ‘authorities’ to respond to their concerns and demands.
Accepted: 2021-02-02T10:30:54Z
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Health sector analysis: political economy of decentralised health service provision - MAP Consult; Konung International (POTENCIAR, 2021)
This report offers POTENCIAR and the British High Commission (BHC) an analysis of how power arrangements influence the main social, political, and economic factors in service provision and decentralised governance in Mozambique. The results of the study will be used to refine POTENCIAR’s strategy and approach, as well as the design of PAIs in the health sector. While PAIs address issues across multiple sectors, sector analysis will also consider potential entry points for, as well as barriers to, the improvement of intersectoral coordination and strengthening of citizen participation. Through an analysis of the political economy of the health sector, this report will examine the formal and informal power structures and institutions that influence service provision and the decentralised governance of the health sector. Methodologically, the study is based on a bibliographic and documentary review of governance, decentralisation, and accountability across Mozambique, and the health sector in particular. These data are complemented by interviews with key informants who have knowledge of or actively participate in the health sector. The study is based on the northern province of Nampula, which POTENCIAR has identified for the implementation of its first pro-accountability initiative in the health sector.
Keywords: *non-public; G - Mozambique / Moçambique; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - health services / serviços de saúde; health / saúde

Inverted State and Citizens’ Roles in the Mozambican Health Sector - Dias, Jose; Tomé, Tassiana (IDS Bulletin, 2018)
This article aims to understand the inversion of roles between the state and citizens, by exploring its historical roots and current implications for processes of social accountability in Mozambique, particularly in the health sector. This is a practice-based reflection grounded in the evidence collected through the implementation of Community Scorecards in the health sector in 13 districts of Mozambique. The evidence has revealed a transfer of responsibilities from local governance institutions and service providers to the communities; diluting the frontiers between the state and citizens’ duties and rights, resulting in the inversion of roles. This inversion results in the minimisation of the state’s performance of its duties and accountability in the health sector to respond to local communities’ needs, allegedly due to the lack of financial resources. It also leads to the overburdening of local communities, who assume the responsibility of meeting their own demands, risking participation fatigue.
Accepted: 2018-05-01T10:02:21Z Publisher: Institute of Development Studies
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; Important; L - english / inglês; Northern PEA; accountability / responsabilização; health / saúde

For an efficient, decentralised, transparent and inclusive health system - N'weti (N'weti, 2016)
Recommendations: 1. On planning and budgeting, greater coordination is recommended between planning (setting priorities) and budgeting (financial apportionment). Transformation of all District Health Services, Women and Social Action (SDSMAS) into Management Beneficiary Units (MBU) is necessary. 2. Stakeholders should bet more on application of national public financial management systems (PFM). The use of parallel financial systems instead of enabling the National Health System (NHS) to be more e cient hinders the enhancement of the sector’s PFM systems. 3. With regard to budgeting, zero-based budgeting implementation is recommended, replacing the incremental budgeting system. Zero-based budgeting is more realistic in so far as the health sector operation costs are concerned. 4. On the decentralisation and citizen participation component, the establishment of a national plan for decentralisation in the health sector is recommended. This plan would allow systematise local citizen participation mechanisms in the health system management and monitoring. 5. On revenue collection, the sector authorities need to explore areas of potential revenue already identified in Intellica’s 2013 research report, such as drug prescription, outpatient, medical certificate rates; and comply with the Decree 11/2007 of 30 May, which regulates tobacco consumption and sale, which has great potential to generate revenue for the health sector at the district level, by means of fines on the lawbreakers. 6. A Policy Brief drawn from the Public Expenditure Tracking Survey (PETS) in the Health Sector in Angoche, Bilene, Magude and Xai-Xai districts, and Chamanculo and José Macamo General Hospitals On expenditure performance, more and better coordination among stakeholders at district levels and Health Centres is recommended in order to avoid expenditure implementation costs in a fragmented and uncoordinated manner. 7. On procurement, accuracy improvement is recommended for the current legal framework implementation. This is to ensure that Procurement Management Units (PMUs) are practical; they can perform their tasks with independence, impartiality and professionalism. The direct award should always be treated as provided for in the law (an exception) and not deemed as the rule like what we have noticed occur in the researched cases. The document disorderliness of the Procurement Management Units portfolios can be solved with portfolio digitisation, ensuring more and better file and document handling, more control and additional transparency. 8. On transparency, recommendation to the Ministry of Health (MoH) is on the establishment of mechanisms which may ensure that sector o cials, who handle equal duties, should have the same understanding about procedures, not only in the health sector, but also in liaison with other sectors and society in general. When applying the Right to Information Act, Civil Society Organizations (CSOs) should now carry out awareness raising sessions and dialogue with sector o cials in order to reach mutual understanding on the added value that represents transparent public service management, with accountability and civil society influence, through monitoring and evaluation.
Keywords: *indexed; *non-public; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Angoche; GD - Bilene; GD - Magude; GD - Xai-Xai; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; budget / orçamento; decentralization / descentralização; health / saúde

N’weti’s Community Scorecard Experience in Nampula: a Case Study - Franco, Erika Lopez; Dumangane, Sansão (Institute of Development Studies and N'weti, 2015)
This case study was commissioned by N’weti Comunicação para a Saúde to explore the changes emerging from the implementation of an adapted version of the Community Scorecard (CSC) tool in 11 health facilities catchment areas in Nampula. This case study discusses how N’weti has adapted the Community Scorecard (CSC) tool to better improve the quality of the participation and prospects of accountability for citizens. The case study presents evidence that the adapted CSC tool has resulted in an increased awareness of rights, an improved relationship with the service providers, a revitalisation of the health unit Co-management Committees, citizens feeling that their voice is being heard, and N’weti is recognised by people and authorities as catalyser and legitimate mediator of this voice. However, challenges also surfaced which N’weti must reflect and learn from. The first relates to the meaningful control from regular citizens (rather than NGO staff members) of the institutionalisation, follow-up of commitments and advocacy actions derived from the implementation of a CSC process. Other challenges refer to social exclusion, the lack of a deeper understanding of power dynamics, and the fact that ignoring previous histories of citizen engagement and other contextual factors can be misleading as not all change can be directly attributed to the implementation of the CSC.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Meconta; GD - Moma; GD - Rapale; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde; social inclusion & exclusion / inclusão e exclusão social